Preliminary Pages - Gori, Maja (Ex Novo: Journal of Archaeology, 2024)
Maja GORI, Daniela HEILMANN, Kristina Penezić Balkan Archaeology as a laboratory ......................................................................................1 Staša Babić Plus ça change? Balkan archaeology in search of identity..........................................................5 Monika Milosavljević Kuhn, Fleck and Archaeological Evidence: An Omnivorous Strategy to Study the History of Archaeology........................................................................................................................17 Christos Giamakis Bridging the Gap(s) between ‘European’, ‘Balkan’ and ‘Greek’ Archaeolog(ies)y...................31 Uroš Matić Queering Serbian Archaeology: Androcentrism, Heteronormativity, Gender and the Writing of (Pre)history.........................................................................................................................53 Reviews Maja Gori Review of Greenberg R. & Hamilakis Y. Archaeology, Nation, and Race: Confronting the Past, Decolonizing the Future in Greece and Israel. Cambridge, 2022...................................77 Daniela Heilmann Review of Gyucha A. & Parkinson W.A. (eds.), First Kings of Europe. From Farmers to Rulers in Prehistoric Southeastern Europe. Cotsen Institute of Archaeological Press, The Field Museum of Natural History. Los Angeles, 2022.................................................................81